Análisis comunicacional del balón y el estadio como simbologías y representaciones que forman parte del fútbol - Herrera Gallo, César Andrés (2015)
How the symbols created around soccer can influence in the mode of being of society? Nowadays, soccer is considered as the king of sports by almost the entire global society. In the practice of this sport there are symbols and representations. Some of them have become in sources of manipulation for interests of certain groups This article has as the main topic backgrounds and analyze symbols and representations that are part of this social phenomeno called soccer. The elements that its considered in this investigation are as the ball, the pitch and clothing. Well, these are the signs of this sport that are involved in the daily life of society. Also, it is analyzing its ability to join the masses. In fact, this sport has the capacity to go foward of important components in human life like: religion, cultures, social class, lenguages, etc. It is taken into consideration its controversial character because it has been an ideological object use by power groups.